Exploring the Relationship Between English Slang on Social Media and Language Acquisition Among Teenagers - Damayanti, Lutfiah; Ekawati, Anita Dewi (Journal of Language and Literature Studies, 2025)
The phenomenon of slang usage on social media has become an integral part of teenage life. Platforms like Instagram, TikTok, and X (Twitter) serve as communication hubs that foster informal and creative language expressions, including slang. Although often seen as non-standard language, slang reflects social dynamics and group identity and has potential implications for English language learning, particularly in vocabulary acquisition and communication skills. This study aims to examine the correlation between the use of slang on social media and English language learning among teenagers. It further investigates whether this correlation is positive, negative, or neutral in terms of language acquisition outcomes. The study adopts a quantitative correlational approach using a survey design. Participants include over 300 teenagers aged 15 to 18 years who are active on social media and enrolled in English language learning programs. Data were gathered using a structured Likert-scale questionnaire consisting of two sections: frequency of slang usage and its perceived influence on English learning. Data analysis involved Pearson Product Moment correlation tests with assistance from SPSS software. Preliminary findings show that teenagers frequently use slang in digital communication, especially in the form of abbreviations and word modifications. This research contributes to the development of curriculum and learning strategies that are more contextual and relevant to the digital lives of adolescents. Slang can be selectively utilized to increase students' motivation and engagement in learning English. However, the scope of this study is limited to adolescents in the JABODETABEK area, so the results need to be generalized with caution. Further research with a more diverse sample is recommended to expand the findings. It provides a basis for designing instructional strategies that leverage slang as a learning tool while mitigating its adverse effects on formal language skills.